Distonia focal e outros transtornos musculoesqueléticos em músicos de orquestra - Marcia Regina Coimbra Cortez (2015)
Introduction: Orchestra musicians, as well as other performing artists are prone to the development of painful symptoms associated with musculoskeletal disorders (MSD) and focal or musician's dystonia (MD). MD is a neurological disorder characterized by involuntary and sustained contractions of restricted muscle groups, painless incoordination and loss of voluntary motor control in extensive musical training movements during the act of playing an instrument. Intensive fine motor training skills, labor infrastructure, body biomechanics, psycho-emotional and possibly genetic factors seem to predispose the triggering of this movement disorder. MD affects 1% to 2% of professional musicians and, in majority of cases, terminates their careers. Aim: To determine the frequency of MSD and MD in orchestral musicians. Methods: Volunteers musicians of three orchestras (n=50, MG) and age and gender matched controls (n=50, CG) were recruited. None of the controls received musical training. All subjects were interviewed according to a specific protocol. The examination of craniomandibular structures (temporomandibular joints - TMJ) was conducted by the researcher, dentist surgeon and also musician. The neurological examination was performed by two neurologists. A questionnaire covering health-related quality of life (HRQL) was adopted: Health survey standard Version (SF-12v2). All subjects gave written informed consent. Results: We found that 86% of MG were affected by pain/MSD versus 54% of CG. In 32 body regions, the musicians displayed a number of regions affected by MSD (180/32) superior to non-musicians (59/32) in a ratio of more than 3 times (3.05) with p<0.001. Of a total of 15 macro body regions affected by MSD (RMSD) there were values significant greater in 8RMSD. In 6RMSD of the 8RMSD were affected only the MG in comparison to GC with p=0.002 and p<0.001. The female gender was more affected by pain/MSD both in the GM (p=0.028) as GC (p<0.001). It was found a frequency of 8% of focal dystonia (FD) in the sample MG. All affected individuals were male. FD was not found in the CG. The HRQL demonstrated that the GM presented a higher score than the GC with p<0.001. Conclusions: Professional musicians feature high frequency of pain/ MSD and MD. This may be related to various risk factors: genetic, occupational, emotional, environmental, and others.